Ukushela: Men's ways of initiating romantic relationships - Ndhlovu, Sizakele (Department of Psychology, 2026)
The initiation of romantic relationships has undergone significant transformation, especially with the rise of online platforms that have reshaped traditional courtship practices. Despite these evolving methods, gender roles continue to shape relationship formation, with societal expectations positioning men as initiators and women as responders. This qualitative study explored how men navigate the initiation of romantic relationships to see whether their approaches will reinforce or challenge dominant discourses of masculinity. Through focus group discussions with thirty male university students (ages 18-35) at the University of Cape Town, the research found that relationship initiation has shifted from formal, structured processes to more casual, everyday interactions. While participants acknowledged the potential benefits of equal participation in relationship formation, they also expressed resistance to changes in established gender practices, particularly regarding emotional expression and financial responsibilities. Young men experience significant pressure to conform to societal expectations of masculinity, both in face-to-face interactions and on digital platforms. These findings highlight how young men both reinforce and challenge dominant masculine discourses during relationship initiation, underscoring the tensions between evolving social norms and persistent gender expectations.